Prevalence of Anxiety and Depression among the Patients Attending Surgical Ward at Public Sector Tertiary Care Hospitals in Karachi (Medical Forum Monthly, 2024)
Objective: To highlight the prevalence of depression and anxiety among patients admitted in a surgical ward of a hospital.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Surgery at Major Tertiary Care Hospitals in Karachi, from March 2018 to September 2018.Materials and Methods: A written informed consent was obtained from each and every patient. A total of 250 questionnaires were distributed of which 210 were returned (Response rate = 84%). But only 198 were complete and thus included in the study. Patients were enrolled by non-probability convenient sampling majority of which were postoperative (n=178). The patients of both sexes who were greater than 15 years of age were included in the study. The Urdu version of Hospital Anxiety and Depression Scale (HADS) was used to measure the severity of anxiety and depression. The score obtained from each patient was used to categorize non-cases (0-7), mild anxiety and mild depression (8-11), moderate anxiety and moderate depression (12-16) and severe anxiety and severe depression (17 and above) cases.Results: The studied patients comprised of 144 (72.7%) males and 54 (27.3%) females. The mean age of the patients was 31.36 ±12.31. The mean score of HADS anxiety was found to be 8.49 ± 3.47 whereas for depression, the mean score was 8.44 ± 3.39. Out of 198, 60 patients were identified as non-cases of anxiety and 73 as non-cases of depression whereas 138 and 125 were determined to be cases of anxiety and depression respectively. The duration of the disease was found to be significantly associated with the HADS scores for anxiety and depression (p value= <0.001).Conclusion: The study was conclusive that staying in hospital and undergoing a surgical procedure does produce anxiety and depression in otherwise healthy individuals and it was also found that duration of disease had a significant impact on the psychological state of the patient.